Framework for genetic improvement of oil yield and harvestability in oil palm - Teh, Chee Keng (2022)
Oil palm (Elaeis guineensis Jacq.) contributes 35% of global vegetable oil and has become the most important oil crop in the world. It occupies only 7% of total global oilseed-harvested land with 10 times more oil yield per hectare of cropland than any other oil crop. To further improve the superior oil yield, enormous efforts have been put into selective breeding programmes in the last eight decades. Nevertheless, the breeding progress of oil palm, like other perennial crops, is extremely slow (typically 12 years per breeding cycle) and costly. In this study, major QTL (quantitative trait loci) for trunk height (THT) and correlated yield traits were discovered in low trunk increment breeding populations using single nucleotide polymorphism (SNP) and simple sequence repeat (SSR) markers. Further understanding of the correlation between THT and oil yield traits, and the effect of cumulative positive alleles of QTL can significantly increase the success rate of multiple trait integration through MAS to produce high-yielding oil palms with low height increment. This compares to an estimated 1% probability of success using conventional breeding methods. Furthermore, illegitimacy in breeding crosses and commercial seed production can be a common problem, if mismanagement happens in controlled pollination (given that oil palm is a naturally outcrossing species) and seed processing. For perennial crops such as oil palm, the illegitimacy problem can easily badly effect a 12-year breeding cycle and illegitimacy can lead to a 25-year yield reduction in commercial planting. Therefore, a practical genomic SNP-based legitimacy testing method with accuracy >97% was developed as a standard quality control procedure for seed purity in breeding and commercial seed production. The method has also successfully addressed the inaccuracy and inefficiency of the conventional fruit census test for contamination. The overall objectives of this study and findings are reported in the thesis.